Mora en París (1834-1850) un liberal en el exilio. Un diplomático ante la guerra - Rojas, Rafael (El Colegio de México, A.C., 2012)
This paper guides us through José María Luis Mora's exile, mainly in Paris and London, from 1834 until his death in the French capital, on July 14th, 1850. The work's sources are mainly the great Mexican liberal's correspondence during those years, read here in searchof deeper insights into Mora`s positions on several topics: natural rights of man, material conditions of exile, edition of his own work and that of the other Mexican an Spanish-American authors, and views of Mexican politics during the first Federal Republic, the Centralist Republic, the wars against the United States and France during the July Monarchy of King Louis-Philippe, and the 1848 Revolution. This paper also offers an assessment of the scarcely acknowledged influence of the French between the young lettered man's anti-corporate liberalism, and the pragmatic diplomacy, favoring Mexican interests, expressed during the veteran statesman's last years.